2016
DOI: 10.1016/j.medengphy.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic interactions between red blood cells and drug carriers by image analysis techniques

Abstract: Blood is a complex biological fluid composed of deformable cells and platelets suspended in plasma, a protein-rich liquid. The peculiar nature of blood needs to be considered when designing a drug delivery strategy based on systemically administered carriers. Here, we report on an in vitro fluid dynamic investigation of the influence of the microcapillary flow of red blood cells (RBCs) on micron sized carriers by high speed imaging methods. The experiments were carried out in a 50 m diameter glass capillary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…Experimentally, the interaction between RBC and NPs or spherical -particles (-Ps) (0.5 to 3 m) shows the blood flows around the RBCs, transiently carrying suspended NPs in closer proximity to the vessel wall where binding can occur [48,79]. RBCs are "super-carriers" [80], can go everywhere, avoiding being trapped in liver and spleen [81].…”
Section: The Role Of the Rbcs In Carrying And Transferring Npsmentioning
confidence: 99%
“…Experimentally, the interaction between RBC and NPs or spherical -particles (-Ps) (0.5 to 3 m) shows the blood flows around the RBCs, transiently carrying suspended NPs in closer proximity to the vessel wall where binding can occur [48,79]. RBCs are "super-carriers" [80], can go everywhere, avoiding being trapped in liver and spleen [81].…”
Section: The Role Of the Rbcs In Carrying And Transferring Npsmentioning
confidence: 99%
“…Previous studies showed that their interactions depend on numerous factors including drug carriers' size, shape, and even vessel geometry (Tan et al 2013). Both numerical simulations and experiments indicated clear interactions between drug carriers and RBCs (Müller et al 2014;D'Apolito et al 2016). Lee et al studied that the cross-sectional distribution of drug carriers depend on their size, and that larger particles tend to marginate towards vessel walls (Lee et al 2013).…”
Section: ;mentioning
confidence: 92%
“…Recently, it were reported that RBCs to affect the transport and distribution of micro carriers in drug delivery process in human microvasculature [138,141]. In fact, while in the absence of RBCs, drug carrier velocity profile superimposes the parabolic Poiseuille profile, just following the motion of the fluid, a remarkable lowering of velocity profiles occurs in the presence of RBCs, due to the increment of suspension viscosity.…”
Section: Cells Motionmentioning
confidence: 99%